Exploring Smart Contracts In Islamic Finance: Blockchain-Based Shariah-Compliant Transactions - Desky, Harjoni; Hye, A. K. Mahbubul (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
The rapid advancement of blockchain technology presents new opportunities and challenges for the Islamic financial system, particularly in ensuring compliance with Shariah principles. As Islamic finance continues to grow, there is a pressing need to explore how digital innovations such as smart contracts can be integrated without violating core religious tenets. This study explores the potential application of smart contracts in Islamic finance, focusing on how blockchain technology can support transactions that comply with Shariah principles. Using a qualitative approach with triangulation methods, the research combines systematic literature review, in-depth interviews, and comparative analysis between smart contract frameworks and classical Shariah contracts such as murabaha, mudarabah, and ijarah. The study examines how smart contracts can enhance transparency, reduce operational costs, and minimize human error while ensuring adherence to Islamic legal and ethical standards. The findings indicate that blockchain-based smart contracts can effectively automate Islamic financial transactions when designed with proper attention to the prohibition of riba (interest) and gharar (uncertainty). The research highlights the need for close collaboration between Shariah scholars and technology developers to ensure compliance. This study suggests that smart contracts hold significant promise for increasing efficiency, trust, and transparency in the Islamic financial ecosystem